الكفاءة اللازمة توافرها لمعلم اللغة العربية لغير الناطقين بها - Imam Wahyudi; Ahmad Mizan Rosyadi Abdul Jalil Manan (Al-Fusha : Arabic Language Education Journal, 2020)
Teacher is the foundation in teaching and learning process who plays the important roles of primary and secondary elements in learning process. By having experience and competence, a teacher can transfer language to students well. A purpose of learning will not be reached without the role of a teacher with relevant competence. In second language teaching, especially in teaching Arabic to non-native speakers, it requires a professional expert as the purpose of second language teaching will not meet success unless managed by a teacher who has experience, has learned the teaching method, and has full comprehension in the characteristic of language he teaches.Therefore, the competence of Arabic teacher to non-native speakers is compulsory to have for anyone who teaches the language. There are at least three competences to have by an Arabic teacher to non-native speakers including, first, academic competence, that covers the language mastery learned for approximately four years during undergraduate study and includes the branches of linguistics, like Grammar, Morphology, Phonology, etc;. Second, professional education competence, that includes understanding and mastering various methods and teaching strategies of second language, learning children-related fundamental theory, like Education Psychology, Developmental Psychology, Education Evaluation, etc; and, Third, culture competence.